Urothelial Carcinoma Recurrence in an Orthotopic Neobladder without Urethral or Upper Urinary Tract Involvement - Chirag P. Doshi; Guliz A. Barkan; Marcus L. Quek (Case Reports in Urology)
We describe a case of a 71-year-old male with an isolated recurrence of urothelial carcinoma in an ileal neobladder without involvement of the upper urinary tract or urethra. He was diagnosed with high grade urothelial carcinoma involving a bladder diverticulum with associated carcinoma in situ. He underwent a radical cystectomy and orthotopic Studer ileal neobladder. On routine follow-up, 11 years following cystectomy, voided urine cytology was positive for high grade urothelial carcinoma. Further workup revealed normal upper urinary tracts, normal urethra, and a solitary lesion at the left anteroinferior wall of the neobladder. He subsequently underwent resection of the neobladder and conversion to an ileal conduit with pathology confirming the diagnosis of high grade urothelial carcinoma. Isolated recurrence of urothelial carcinoma within a neobladder without involvement of the upper urinary tract or urethra is rare. No guidelines exist regarding its management. Herein we present our management as well as the current literature published on this topic.